Jakość kształcenia w świetle przemian w polskim szkolnictwie wyższym - Kwiatkowska, Magdalena (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The article is about the transformation of the Polish higher education and the changes made in the direction of educating librarians and information professionals. Changes taking place are the result of the inclusion of the Polish universities in the Bologna process, which is a program designed to create a European Higher Education Area.